2016
DOI: 10.12688/f1000research.8657.1
|View full text |Cite
|
Sign up to set email alerts
|

Priority regions for research on dryland cereals and legumes

Abstract: Dryland cereals and legumes  are important crops in farming systems across the world.  Yet they are frequently neglected among the priorities for international agricultural research and development, often due to lack of information on their magnitude and extent. Given what we know about the global distribution of dryland cereals and legumes, what regions should be high priority for research and development to improve livelihoods and food security? This research evaluated the geographic dimensions of these crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…5). This is in line with Walling and Kleo's (1979) global study of sediment yield and climate, which also shows a further major peak at ~ 800 mm yr -1 attributed to the most expansive agricultural production globally (Hyman et al, 2016). In contrast to Walling and Kleo (1979), which does not isolate the effects of variable land use, topography, and geology on sediment yields, our use of long-term erosion rates means that we can largely ignore the effects of land use.…”
Section: Erosion and Precipitationsupporting
confidence: 88%
“…5). This is in line with Walling and Kleo's (1979) global study of sediment yield and climate, which also shows a further major peak at ~ 800 mm yr -1 attributed to the most expansive agricultural production globally (Hyman et al, 2016). In contrast to Walling and Kleo (1979), which does not isolate the effects of variable land use, topography, and geology on sediment yields, our use of long-term erosion rates means that we can largely ignore the effects of land use.…”
Section: Erosion and Precipitationsupporting
confidence: 88%
“…Sorghum ( Sorghum bicolor ) and millets ( Pennissetum glaucum, P. typhoides, P. tyhpideum, P. americanum and Eleusine coracana ) are grown by tens of millions of smallholder farmers in South Asia and Sub-Saharan Africa (SSA) ( ICRISAT & Partners, 2017 ). 1 They are grown primarily in the semi-arid and sub-humid agro – ecologies ( Gumma et al, 2017 ) where their adaptability to high temperatures and drought ( Hyman et al, 2016 ) makes them resilient to climate change ( Adhikari, 2015 ). One-third of the population in these areas live below the international poverty lines of $1.25 per day ( Gumma et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The regions where these crops are grown are prone to drought and heat stress, have limiting soil constraints, contain half of the global population, and account for 60% of the planet’s poor and malnourished people (Hyman et al, 2016). A recent study involving six major crop commodity groups in 131 countries reported losses from 1961–2014 of 1.6% in cereal production, 0.5% in oil crops, 0.6% in pulses, 0.2% in fruits, and 0.09% in vegetables due to drought and heat disasters.…”
Section: Introductionmentioning
confidence: 99%